2018
DOI: 10.1007/s13197-018-3532-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mild roasting on Arabica and Robusta coffee beans contamination with polycyclic aromatic hydrocarbons

Abstract: The aim of this research was to establish the effect of mild roasting on coffee beans contamination level by polycyclic aromatic hydrocarbons (PAHs). The materials investigated were green Arabica and Robusta coffee beans imported from different countries, as well as those already roasted. The experiment was carried out in a coffee-roasting plant, with the use of an electric coffee roaster, at the temperature of 125–135 °C for 25–26 min. PAHs analysis was conducted by means of high-performance liquid chromatogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…As PAHs are ubiquitous pollutant compounds, their occurrence in green coffee beans is mainly due to environmental contamination, and the various studies that have been reviewed herein have indicated that, when present, PAHs content in such matrices is low. An overview of PAHs amount in coffee of different origins can be found in an interesting work by Ciecierska et al (2019), which demonstrated that Kenya and Tanzania (both Eastern Africa) for Arabica green samples, and the Ivory Coast (south coast of West Africa) and Cameroon (Central Africa) for Robusta samples, were the most contaminated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As PAHs are ubiquitous pollutant compounds, their occurrence in green coffee beans is mainly due to environmental contamination, and the various studies that have been reviewed herein have indicated that, when present, PAHs content in such matrices is low. An overview of PAHs amount in coffee of different origins can be found in an interesting work by Ciecierska et al (2019), which demonstrated that Kenya and Tanzania (both Eastern Africa) for Arabica green samples, and the Ivory Coast (south coast of West Africa) and Cameroon (Central Africa) for Robusta samples, were the most contaminated.…”
Section: Discussionmentioning
confidence: 99%
“…4). Moreover, an electron Table 2 Effect of mild roasting conditions on samples from different countries: green vs roasted coffee beans PAHs contamination level, standard deviations are not reported (Ciecierska et al, 2019 spin resonance (ESR) experiment led to the hypothesis that free radicals may be engaged in this pathway; as shown in Fig. 4, the ESR signal intensity were increased in the coffee model system when amino acids were added and results were correlated to the outcomes on the formation of nitro-PAHs.…”
Section: Formation Of Pahs and Derivatives During Coffee Roastingmentioning
confidence: 97%
See 2 more Smart Citations
“…Tfouni et al [72] reported no statistically significant difference in PAHs levels of coffee brews produced from beans roasted at different temperatures. Ciecierska et al [73] described that roasted coffee beans had significantly lower levels of contamination than green coffee beans, indicating that the roasting process can significantly reduce the levels of PAHs in the final product. This is attributed to the high volatility of light PAHs.…”
Section: Drying and Roasting In Grainsmentioning
confidence: 99%